Interference effects between two high-rise buildings on wind-induced torsion. Issue 159 (December 2016) - Yu, X.F.; Xie, Z.N.; Wang, X.; Cai, B.
Abstract: The distribution variation and correlation of envelope interference factor ( EIF ) of the base torsion responses for principal building were studied by applying the rigid model wind tunnel test. The influence factor including different breadth ratio ( B r =0.4, 0.6, 0.8, 1.0, 1.2 and 1.4), height ratio ( H r =0.8, 1.0, 1.2 and 1.4), reduced velocity and approaching turbulence intensity were considered. Furthermore, the mechanism and occurrence condition of wake vortex-excited resonance were also studied. Results showed that the maximum value of EIF was 1.9 when vortex-excited resonance failed to happen. The correlation coefficient of EIF between B r =0.8 and B r =1.0 was 90.2%. Vortex-excited torsion resonance which induced from wake of interfering building occurred when B r =0.4, and the maximum value of EIF reached up to 2.98. With increased H r, the value of EIF increased. Good correlation was shown among different height ratios. For breadth ratios range from 0.3 to 0.5, it was suggested the reduced velocity should be out of the range of 3.33–5.56 to avoid occurring vortex-excited torsion resonance. Highlights: Interference effects on wind-induced torsion in various arrangements. The maximum EIF is 1.9 when vortex-excited resonance fails to happen. The maximum EIF reaches up to 2.98 when vortex-excited torsion resonance occurs. Good correlation is shown among different height ratios. Reduced velocity should be out of the range of 3.33~5.56.